Management of retroperitoneal fibrosis with endovascular aneurysm repair in patients refractory to medical management - Sultan, Sherif; Acharya, Yogesh; Hezima, Mohieldin; Ramjohn, Joshua; Miresse, David; Chua Vi Long, Keegan; Soliman, Osama; Hynes, Niamh (Frontiers in Surgery, 2022)
Background: Early diagnosis and treatment of under-recognized retroperitoneal fibrosis (RPF) are essential before reaching the poorly responsive fibrotic stage. Although most patients respond to medical therapy, relapses and unresponsiveness are common. However, open surgery in medically resistant patients is associated with major adverse clinical events. Methods: This is a single-centre longitudinal study of optimal medical therapy (OMT) vs endovascular aneurysm repair (EVAR) in patients presenting with RPF to our tertiary referral vascular centre. Out of 22,349 aortic referrals, we performed 1555 aortic interventions over twenty years. Amongst them, 1006 were EVAR, TEVAR and BEVAR. Seventeen patients (1.09%) had documented peri-aortic RPF. Results: Out of the 17 RPF patients, 11 received OMT only, while 6 underwent EVAR after the failure of OMT. 82% (n=14) were male, and the median follow-up was 62.7 months (IQR: 28.2 – 106). Nine (52%) had immunoglobulin G4-related disease (4 OMT vs 5 EVAR). EVAR patients had 100% technical success without perioperative mortality. Furthermore, all the EVAR patients were symptom-free following the intervention. Pre-operative aortic RPF index (maximum peri-aortic soft tissue diameter/maximum aortic diameter) was higher in the EVAR than in OMT. However, there was a significant decrement in the aortic RPF index following EVAR (p=0.04). Conclusion: We believe that when optimal medical therapy fails in RPF, EVAR provides a promising outcome. Further studies are recommended to establish the role of endovascular repair.